The Problem of Affordable Education in Indonesia: The Emergence of Online Tutoring Service in Primary Education Level - Cathrin, Shely; Hanum, Farida; Dwiningrum, Siti Irene Astuti; Efianingrum, Ariefa; Suyantiningsih, Suyantiningsih; Hayashi, Masami (Asosiasi Dosen PGSD dan Dikdas Indonesia, 2023)
The development of online tutoring services suggests that Indonesian education faces significant challenges. The purpose of this study is to investigate the issue of educational affordability that arises as a result of the creation of numerous tutoring services in Indonesia. This study used a descriptive research model and a qualitative methodology. This research data takes the form of literature from studies on the existence of elementary school tutoring institutions in Indonesia with all its issues, which are examined from a phenomenological point of view. The findings indicated that public mistrust in the caliber of education provided in formal schools contributed to the rise of online tutoring services at the elementary school level. Students are beginning to choose to employ online tutoring services due to tedious coursework and the ineffectiveness of learning implementation in traditional elementary schools. This article suggests that the government cooperate with the private sector and education innovators to create media and learning methods that are efficient, enjoyable, and still affordable for everyone to address the deficiencies in Indonesia's formal education system.